2018
DOI: 10.1021/acsmedchemlett.8b00175
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetics for Targeting Protein–Protein Interactions between DOT1L and MLL Oncofusion Proteins AF9 and ENL

Abstract: MLL-fusion proteins, AF9 and ENL, play an essential role in the recruitment of DOT1L and the H3K79 hypermethylation of MLL target genes, which is pivotal for leukemogenesis. Blocking these interactions may represent a novel therapeutic approach for MLL-rearranged leukemia. Based on the 7 mer DOT1L peptide, a class of peptidomimetics was designed. Compound with modified middle residues, achieved significantly improved binding affinities to AF9 and ENL, with K values of 15 nM and 57 nM, respectively. Importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…We have successfully developed the first class of peptidomimetics that target PPIs between DOT1L and MLL onco-fusion proteins, AF9 and ENL, based on the 10mer DOT1L peptide [ 40 ]. The findings of this study provide further evidence validating the rationale for a novel promising strategy that disrupts interactions between DOT1L and AF9 in MLL fusion protein-associated leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have successfully developed the first class of peptidomimetics that target PPIs between DOT1L and MLL onco-fusion proteins, AF9 and ENL, based on the 10mer DOT1L peptide [ 40 ]. The findings of this study provide further evidence validating the rationale for a novel promising strategy that disrupts interactions between DOT1L and AF9 in MLL fusion protein-associated leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…This study further confirmed that DOT1L recruitment by AF9 is necessary for MLL-AF9 mediated colony-formation and leukemic transformation. Recently we reported a class of peptidomimetics based on the 10-mer DOT1L binding peptide, providing a proof-of-concept for the development of nonpeptidic compounds to inhibit DOT1L activity by targeting its interaction with MLL-oncofusion proteins, AF9 and ENL [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal chemistry optimization yielded a series of 7-mer peptidomimetic compounds 21 and 28 (Fig. 12 e) against the interaction between AF9/ENL and DOT1L with IC 50 values as low as 57 nM [ 197 ]…”
Section: Ppis Involving Mll1 Fusion Proteinsmentioning
confidence: 99%
“…In recent years, new compounds with different mechanisms of action have been developed. Unlike the first class of DOT1L inhibitors, mimetic peptide molecules such as compound (8), shown in Figure 3, do not determine total inhibition of DOT1L activity, but bind AF9/ENL, thus blocking recruitment of DOT1L to MLL target genes and reducing levels of HOAX9 [110].…”
Section: Dot1l Inhibitorsmentioning
confidence: 99%